2021
DOI: 10.21203/rs.3.rs-209379/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Remimazolam Besylate Versus Propofol during Hysteroscopy: Single‐centre Randomized Controlled Trial

Abstract: Background: Remimazolam besylate is a new type of benzodiazepine that has the characteristics of quick effects, short maintenance and recovery times, and no accumulation. Compound opioids can have a sedative effect in some endoscopic examinations. This trial was conducted to confirm the efficacy and safety of remimazolam besylate versus propofol during hysteroscopy.Methods: Patients undergoing hysteroscopy were randomly assigned to either the remimazolam (Group R, n=41) or the propofol group (Group P, n=41). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
(25 reference statements)
4
15
1
4
Order By: Relevance
“…The incidence of respiratory suppression in groups B and C was lower than that in group A, and there was no injection pain occurred in groups B and C. These indicated that the adverse events incidence of remimazolam tosylate was lower, especially in the low-dose remimazolam tosylate group. This result is consistent with the results of the study by Zhang et al 19 that remimazolam tosylate is a safer alternative to anaesthesia during hysteroscopy. On this basis, our study further investigated the recovery speed of remazolam and the better sedation and maintenance dose.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of respiratory suppression in groups B and C was lower than that in group A, and there was no injection pain occurred in groups B and C. These indicated that the adverse events incidence of remimazolam tosylate was lower, especially in the low-dose remimazolam tosylate group. This result is consistent with the results of the study by Zhang et al 19 that remimazolam tosylate is a safer alternative to anaesthesia during hysteroscopy. On this basis, our study further investigated the recovery speed of remazolam and the better sedation and maintenance dose.…”
Section: Discussionsupporting
confidence: 93%
“…When compared with propofol in both sedation and general anesthesia, remimazolam exhibited better safety profile, including a lower incidence of hypotension, less bradycardia treatment requirement, and no pain on injection [34,36,41]. However, propofol was less likely to develop PONV.…”
Section: Safety Concerns and Future Directionsmentioning
confidence: 99%
“…Therefore, there is a need for safer sedatives while ensuring their efficacy [35]. Clinical studies comparing efficacy and safety of remimazolam vs. propofol for procedural sedation suggested that remimazolam was non-inferior in terms of sedative efficacy and exhibited better safety profile than that of propofol [32,34,36]. Chen et al [32] demonstrated that the procedure success rate in the remimazolam group was similar to that in the propofol group (96.91% vs. 100%, respectively) in 384 patients who underwent colonoscopy [32].…”
Section: Clinical Applications Of Remimazolam Remimazolam For Procedural Sedationmentioning
confidence: 99%
“…Three phase II studies of remimazolam besylate in procedural sedation have been published. The first was in 100 patients undergoing upper gastrointestinal endoscopy ( Borkett et al, 2015 ), the second in 162 patients undergoing colonoscopy ( Pambianco et al, 2016 ), and the third in 82 patients undergoing hysteroscopy ( Zhang et al, 2021 ). A midazolam-treated group was included as a comparator in the first two studies.…”
Section: Remimazolammentioning
confidence: 99%
“…In high-risk patients (ASA class III/IV), a safety profile similar to that in low-risk patients was observed ( Rex et al, 2021 ). Compared with propofol in procedural sedation, remimazolam showed a lower incidence of hypotension, respiratory depression, and injection site pain ( Chen et al, 2020a ; Chen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Remimazolammentioning
confidence: 99%